Analysis of the Shifting Strategy of Civil Society Coalitions in Influencing Internal Police Policies (A Case Study of Disciplinary Regulations and the Code of Ethics) - Iwan Susanto R; Nani Nurani Musin; Rahmat Salam (Al-Makki Publisher, 2025)
This article analyzes the shift in the advocacy strategy of the Civil Society Coalition (KMS) in Indonesia in influencing the internal policies of the National Police of the Republic of Indonesia (Polri). From confrontational street protests, KMS transformed into a more structured, collaborative, and focused approach on regulatory advocacy (lobbying and influencing the Disciplinary Regulations and Code of Ethics). This study aims to explore the factors driving this strategic shift and analyze its impact on internal police reform. Using a qualitative approach with a case study design, data were collected through in-depth interviews, Focus Group Discussions (FGDs), and document analysis. The theoretical framework of Policy Advocacy and Social Networks is used to understand these dynamics. The results are expected to provide in-depth insights into the irreplaceable role of civil society in spurring accountability in law enforcement institutions and increasing public trust. The study found that structured, regulation-based advocacy—supported by multi-stakeholder networks and data utilization—proved more effective than confrontational approaches in driving long-term institutional reform.